(untitled) (International Journal of Engineering and Computer Science, 2017)
The performance of Ad-hoc network is calculated by the number of packets successfully delivered to the destination. In multi-hop wireless networks, every node acts as middle node to forward packets to other nodes. To increase the overall network performance, number of packets delivered to the destination successfully must be increased. In the congested network the coordination between the active nodes must be maintained to increase network performance .In this paper, we discuss medium access protocol, MACA .The Hidden terminal problem and exposed terminal problem had been solved by using MACA. In this paper we review MACA and highlight the NAV attack which is possible in this protocol .We also propose the new technique for the prevention of NAV attack. When triggers the NAV attack in MACA protocol overall network performance degrades. There is an algorithm to detect the selfish nodes and also simulated their approach in NS-2 which shows the efficiency of the algorithm of solution [11]. The attacks exploit the local estimation and global aggregation of the metric to allow attackers to attract a large amount of traffic [10].